Nursing Students’ Critical Thinking, Problem Solving and Self Directive Learning Skills: The Effect of Problem-Based Learning (PBL) Versus Lecture Based Learning (LBL) - Najjar, Hend Al; Khalil, Amal Ibrahim; Bakar, Siti Awa Abu (Issues and Development in Health Research Vol. 5, 2021)
Background: Although there is much literature on Problem-Based Learning (PBL) in medical and nursing education, there is little from the cultural perspective. Therefore, the study objective was to investigate the outcome abilities including critical thinking, problem-solving, and self-directed learning of nursing students receiving PBL vs. traditional lecture. PBL is a student-centered outcome-based learning and has become very crucial for higher learning and proven to improve the quality of learning among students at all levels and in various disciplines. Methods: A randomized controlled trial (RCT) design was used with 85 undergraduate students who studied in level seven and were enrolled to a psychiatric nursing course. Four instruments were used including: 20-items self-report PBL Evaluation Questionnaire (PBLEQ). The Self-assessment Scale on Active Learning and Critical Thinking (SSACT) scale consists of 14 items of two domains “active learning” and “critical thinking.” All scales had good reliability with coefficient alpha >0.8. Results: the survey response rates were 100%, the study results revealed that the experimental group was considered PBL is effective in their learning process (t=3.568; p\(\le\)0.05). The overall SSACT also showed a significant difference in experimental group at pre and post intervention (t=6.413; p\(\le\)0.05). There was also a significantly different percentage score between experimental and control group in pretest (t=2.374 p\(\le\)0.05). Conclusion: This study offers information on student’s perspective regarding the effectiveness of PBL in constructing professional knowledge, developing problem solving skills, developing self-directed learning, and improving motivation. Moreover, it promotes effective group collaboration and enhances active learning and critical thinking. Therefore, PBL is easily considered as an alternative method of teaching nursing students since, it helps students act as professionals in clinical situations with insufficient information and encourages them to think not only deeply, but also rigorously while developing lifelong learning skills.